Implementasi IoT dan EBT Sel Surya Pada Atmi Madi Guna Mendukung Upaya Peningkatan Produksi Pertanian Padi Pada Kelompok Tani Sedya Karya Makmur di Kabupaten Sleman - Irwan Novianto; Marosimy Millaty; Zulfatun Ruscitasari; Aris Kusumo Diantoro; Mauladi Pratama; Erica Herlinawati; Rio Ardiansyah (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Sedya Karya Makmur Farmers Group is a group of rice cultivators whose harvest results are often not optimal due to planthopper pest attacks. Farmers use pesticides to deal with planthopper pest attacks. However, spraying pesticides can damage the environment in the long term. For this reason, the service team offers a solution by making an ATMI MADI tool (Rice Plant Pest Control Tool). This tool is powered by IoT and EBT-based solar cells, which is a system that uses solar power to operate a device that functions as a pest exterminator for rice plants. This tool can emit sound with a sound frequency of around 200Hz to 300Hz based on IoT, and emit light of 570nm to 590nm which can attract pests towards the tool. This tool is equipped with a weighing module to determine the number of pests trapped in the tool. The main advantage of ATMI MADI is that apart from being able to catch rice plant pests, by using IoT you can monitor data on pests caught every day. So it can be used as a pest data bank and help farmers observe patterns of plant pest attacks in the farmer's area just by opening a smartphone or laptop or PC.